1991
DOI: 10.1021/bi00226a002
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a receptor for C5a anaphylatoxin on differentiated HL-60 cells

Abstract: A cDNA clone encoding the human C5a anaphylatoxin receptor has been isolated by expression cloning from a CDM8 expression library prepared from mRNA of human myeloid HL-60 cells differentiated to the granulocyte phenotype with dibutyryladenosine cyclic monophosphate. The cDNA clone was able to transfer to COS-7 cells the capacity to specifically bind iodinated human recombinant C5a. The cDNA was 2.3 kb long, with an open reading frame encoding a 350-residue polypeptide. Cross-linking of iodinated C5a to the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(101 citation statements)
references
References 37 publications
(31 reference statements)
2
96
0
3
Order By: Relevance
“…~101r4iee DNA scqucnce colrc~pondmg to positron I-lob3 of the C&R acqucncc 'I o introduce p,lrt of the nritlvc Ic&r scqucncc al the CS,IK I ng of the rccombmJnt DNA clone wnq rcaniptlllcd by 25 cyctcd PCH ~l*lng Pl end P! ar, a~npl~ficntm pruners and cloned into the HlndlIB rite of pGEM-9Zf(-) Posltlve clones were completely sequenced as described above The final recombmant plasmld, called pCGI, contamed the complete DNA sequence of the C5aR from posltlon -18 to 1063 downstream of the T7 promotor [5] This clone (or a subclone m pCDM8 (Invltrogen) called pCCI) served for the productton of cRNA [7] 2 3 Prcpctratroti OJ RNA U937 cells were grown m RPM1 1640 mcdlum (Chbco) For mduction of CSaR expressIon cells were treated with I mM dlbutyryl.cAMP (Boehrrngcr) for 40 h Total RNA was prepared by the guamduuum lsothiocyanate method [7] and stored at -70°C m water cRNA for the CSaR was prepared from the T7 promotor of the Ns!I-drgested pCGl (or XDaI-dIgested pCCI. rcspectlvely) usmg the mCAP mRNA cappmg kit (Stratagene) and quantitated by densltometruz evnludtlon from ethichum brormde-stained agarose gels against a known RNA standard usmg the CS-I system (Cybertech)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…~101r4iee DNA scqucnce colrc~pondmg to positron I-lob3 of the C&R acqucncc 'I o introduce p,lrt of the nritlvc Ic&r scqucncc al the CS,IK I ng of the rccombmJnt DNA clone wnq rcaniptlllcd by 25 cyctcd PCH ~l*lng Pl end P! ar, a~npl~ficntm pruners and cloned into the HlndlIB rite of pGEM-9Zf(-) Posltlve clones were completely sequenced as described above The final recombmant plasmld, called pCGI, contamed the complete DNA sequence of the C5aR from posltlon -18 to 1063 downstream of the T7 promotor [5] This clone (or a subclone m pCDM8 (Invltrogen) called pCCI) served for the productton of cRNA [7] 2 3 Prcpctratroti OJ RNA U937 cells were grown m RPM1 1640 mcdlum (Chbco) For mduction of CSaR expressIon cells were treated with I mM dlbutyryl.cAMP (Boehrrngcr) for 40 h Total RNA was prepared by the guamduuum lsothiocyanate method [7] and stored at -70°C m water cRNA for the CSaR was prepared from the T7 promotor of the Ns!I-drgested pCGl (or XDaI-dIgested pCCI. rcspectlvely) usmg the mCAP mRNA cappmg kit (Stratagene) and quantitated by densltometruz evnludtlon from ethichum brormde-stained agarose gels against a known RNA standard usmg the CS-I system (Cybertech)…”
Section: Methodsmentioning
confidence: 99%
“…It IS generated by proteolytlc cleavage of the complement component C5 durmg activation of the complement system (see [1] for review) and exerts Its various functions by bmdlng to a specific C5a receptor found In the membrane of several cells, like neutrophils, eosmophlls and the U937 and I-IL60 cell line [2-51 These latter two cell lines express high levels of C5aR If stimulated with CAMP while no C5aR expression can be demonstrated m unstlmulated cells Clomng of the cDNA for the human C5aR from the U937 and HL60 cell lines has recently been reported [4,5]. The CSaR identity of the cDNA clones was demonstrated by their abihty to confer a high-affimty C5a bindmg property to transfected CO § cells Functlonal expression of the CSaR III XUIOJMS oocytes by mlcroiqection of mRNA from CAMP-stimulated HLGO cells has been reported by Murphy et dl [6].…”
Section: Introductionmentioning
confidence: 99%
“…The C3a receptor (C3aR) and the C5a receptor (C5a; CD88) are both GPCRs (15)(16)(17)(18)(19), which couple usually to G i (13) and share ϳ40% sequence identity. There is a third anaphylatoxin receptor, C5L2, which binds C5a, but according to most reports its activation does not cause any cell stimulation (20), suggesting that this may be a scavenger receptor for C5a (21).…”
Section: C3a and C5a Are Chemotactic Factors For Human Mesenchymal Stmentioning
confidence: 99%
“…Binding studies revealed that neutrophils have approximately 40000 C3a receptors and between 100000-300000 CSa receptors (Gerardy-Schahn et al, 1989;Snyderman and Pike, 1984). Recently, the cDNA encoding the human C5a receptor was cloned and classified to the rhodopsin receptor superfamily (Boulay et al 1990; Gerard and Gerard, 1991). C5a induces activation of pertussis-toxin-sensitive G proteins, stimulates phospholipase C, activates phosphatidylinositolbisphosphate 3-kinase (PtdInsP2 3-kinase) and triggers actin polymerization (Dobos et al, 1992).…”
Section: '-0-(3-['5s]thiotriphosphate) (["S Igtp[s])mentioning
confidence: 99%